A comparative analysis of fetal outcomes in pre-eclampsia and eclampsia: insights from vaginal, cesarean, and forceps deliveries - Talukder, Shovana; Ahamed, Nafisa; Khatun, Momena; Saif, Sonia; Saha, Shilpi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pre-eclampsia and eclampsia are significant complications of pregnancy, characterized by hypertension and potential multi-organ dysfunction, which pose serious risks to both maternal and fetal health. This study aimed to analyze fetal outcomes in pre-eclampsia and eclampsia: insights from vaginal, cesarean, and forceps deliveries. Methods: This observational cross-sectional study was carried out in the department of gynaecology and obstetrics at Dhaka medical college hospital, Dhaka, from July 2015 to December 2015. Patients of pre-eclampsia and/or eclampsia who attended the eclampsia ward in the department of gynaecology and obstetrics at Dhaka medical college and hospital, Dhaka were taken as the study population as per inclusion criteria. A total number of 100 patients presented with pre-eclampsia and/or eclampsia fulfilled the selection criteria and were taken as study subjects by purposive sampling method. Different statistical methods were adopted for data analysis. Statistical analysis was performed by using statistical packages for social sciences (SPSS-19). Results: Regarding fetal outcomes, 81.0% of mothers had live births, with 49.0% normal, 19.0% asphyxiated, and 15.0% requiring NICU admission. Nine percent resulted in stillbirths; all linked to intrauterine devices (IUD). Delivery methods included 77.0% vaginal births, 22.0% cesarean sections, and one forceps delivery, indicating a predominant use of vaginal delivery among the patients. Conclusions: The 81.0% of mothers experienced live births, and there were concerning rates of adverse outcomes, including asphyxia and NICU admissions. The high rate of vaginal deliveries (77.0%) raises questions about safety, especially given the stillbirths recorded.